Reconsidering the Link Between Depression and Crime: A Longitudinal Assessment: - Ozkan, Turgut (Criminal justice and behavior, 2019)
A long line of research has uncovered a link between depression and delinquency. However, much of this research has been unable to disentangle the temporal ordering of the depression and crime relationship. In addition, few studies have examined potential mediating relationships between depression and crime, including, for example, theoretical variables such as individual self-control. To address these gaps, we examined depression symptoms as a risk factor for both violent and income-related offenses in a longitudinal framework controlling for several potential confounders using the Pathways to Desistance study that includes information on a unique sample of serious adolescent offenders (N = 1,354). Our findings reveal that depression is inconsistently related to crime in cross-sectional models, but is a risk factor for both aggressive and income-related offenses in a longitudinal framework and that depression has an independent effect on delinquency that is not mediated by self-control.